Membangun Aplikasi E-commerce Menggunakan Framework CodeIgniter ( Studi: Sentra Industri Tas Kendal ) (Information Technology and Telematics, 2014)
Abstrak - Kendal is the industrial center located in thevillage Truko bag. Its existence since 1988, proving thatthe industry is able to compete in a global world. Poweredby abilities and skills, the artisans capable of producingmore than 4300 bags every month. Such a small industry,in marketing and booking transactions are still verymanual.Knowing that this industry is very potential to bedeveloped, therefore the application of E-commerce as amarketing medium that is appropriate, in addition totrading without limitation, e-commerce this also expectedto provide comfort in the users agreement.This E-commerce applications designed using thewaterfall method, because the work of the system is donein a sequence. The application framework is the rightsolution on the management of website, using the conceptof MVC (Model, View, Controller). FrameworkCodeigniter be the best choice because it is easier to usethan other.Kata kunci : e-commerce, waterfall, framework,codeigniter.